2021
DOI: 10.3390/cells10123575
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Processes Induce Complement Activation via Classical Pathway in Porcine Neuroretinas

Abstract: Considering the fact that many retinal diseases are yet to be cured, the pathomechanisms of these multifactorial diseases need to be investigated in more detail. Among others, oxidative stress and hypoxia are pathomechanisms that take place in retinal diseases, such as glaucoma, age-related macular degeneration, or diabetic retinopathy. In consideration of these diseases, it is also evidenced that the immune system, including the complement system and its activation, plays an important role. Suitable models to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…Now, co-staining of complement markers with Iba1 showed that C1q was often co-localized with Iba1 + microglia/macrophages, while only few C3 + or MAC + cells showed co-localization with Iba1. Similar results were noted in a porcine organ culture model, where damage was induced by oxidative stress or hypoxia (58). It is well known that microglia can express complement proteins, including C1q (56, 59, 60).…”
Section: Discussionsupporting
confidence: 82%
“…Now, co-staining of complement markers with Iba1 showed that C1q was often co-localized with Iba1 + microglia/macrophages, while only few C3 + or MAC + cells showed co-localization with Iba1. Similar results were noted in a porcine organ culture model, where damage was induced by oxidative stress or hypoxia (58). It is well known that microglia can express complement proteins, including C1q (56, 59, 60).…”
Section: Discussionsupporting
confidence: 82%
“…Hypoxia induces adaptive response to maintain the homeostasis of intracellular environment and promote cell survival (Kong et al 2022 ; Qureshi-Baig et al 2020 ). For others, hypoxia induces cell death by activating apoptosis (Ren et al 2021 ; Mueller-Buehl et al 2021 ). The research on the changes of metabolic function caused by hypoxia and its mechanism will help to understand the pathogenesis of hypoxic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of changes in the microglial mRNA expression could be due to the CoQ10 concentrations used, the time points, or a difference between cell presence and gene expression. Discrepancies between expression and cellular occurrence were already seen in other studies and might be related to post-transcriptional and translational regulations [31,56,57].…”
Section: Discussionmentioning
confidence: 52%
“…Three sections per explant were stained with hematoxylin + eosin (HE) [31]. The thickness of the retina was measured in three different areas of two photos per section via ZEN 2012 imaging software (Carl Zeiss MicroImaging GmbH, Oberkochen, Germany).…”
Section: (Immuno-) Histological Staining Of Retinal Cross-sectionsmentioning
confidence: 99%